Hybridization-encoded DNA tags with paper-based readout for anti-forgery raw material tracking - Jiaming Li; Alex Crown; Peter Ney; Sergey Yekhanin; Aditi Partap; Anuja Shirole; Huiting Jiang; Sagan Russ; Max Gordon; Adaora Aroh; Jeff Nivala; Anirudh Badam; et al. (Nature Communications)
Abstract Tracking and tracing raw materials is crucial for securing global supply chains. Conventional methods like barcodes and Radio Frequency Identification (RFID) tags are effective but fall short in ensuring raw material traceability and anti-counterfeiting. This work introduces DNA as a powerful tool for source tracking, leveraging its invisibility, safety, and seamless product integration. We present DNATags–engineered DNA mixtures enabling product labeling with error tolerance–readable in the field via paper tickets that fluoresce under a mobile phone and filter device. Additionally, DNATrack employs DNA Hybridization Encoding (HyEn) for enhanced anti-forgery security. Although current costs are higher ($2-$4 per read and write), declining DNA synthesis costs, along with DNA’s unique advantages, make this approach a promising solution for future supply chain management.